The Village Leader as a Safety-Valve in Resolving Conflict of Shelter Aids Post an Earthquake - Suadi Zainal; Risda Feline; Zurriyati A. Jalil; Aizar Khairi (Soshum: Jurnal Sosial dan Humaniora, 2020)
Natural disasters always threaten human life, but sometimes it may prosper people in the disaster area. For example, the earthquake in Aceh, it brought material aids and employment opportunities to Acehnese. However, the aid caused a social conflict due to the aids distribution deemed unfair. In this case, a village leader, as a central figure, demanded his expertise to prevent violence or damage. This research aims to analyze the village leader's roles as a safety valve in handling conflict of shelter aids for earthquake victims. This study was conducted with a qualitative approach that involved fifteen informants as the primary data source. They were the village's apparatus and earthquake victims. The results showed that the village leader as a safety valve, he formed a community group as a new safety valve and offered his people new hope beyond the demands. Thus, this study suggests that the safety valve model may be used to pause the conflict escalates into violent behavior, but not to settle the root causes of conflict. Nevertheless, it may create harmony if the solutions proposed are beyond the promise of voice. For the next researchers, the study suggests examining the effectiveness of hope or promise in conflict resolution for disaster aids management